The international stock market interdependence between Malaysia, Singapore and Indonesia / Mohd Farhan Jafri - Jafri, Mohd Farhan (Faculty of Business and Management, 2009)
The issues of international stock markets linkages had been investigated over the time. Since the Asian financial crisis in 1997, many economists are concerned about the relationship between Asian stock markets and others in the world. This paper is conducted to examine the linkages between Malaysia, Singapore, and Indonesia stock markets. The Vector Autoregression (VAR) model was applied to five years daily price stock index from these three countries from 2004 to 2008. The results show that both a domestic and international price relationship between stock indexes exists in Malaysia, Singapore and Indonesia. Furthermore, the study shows that the current return of Malaysia market is not affected by the previous return of the same market. The result from the finding also indicates that the current return of Indonesia market is not persuading by the previous return from the same market. However, the result shows that the current market return of Singapore market is positively influence by the previous return from the same market. As a conclusion, the result of this study show that the relationship effect exists between stock market in Malaysia, Singapore and Jakarta. This means the investors should be aware of the price movement in stock market between Malaysia, Singapore and Indonesia. The result also indicates that there is international stock market interdependence between these three countries.